The Scanning CONfoCal Ophthalmoscopy foR DIAbetic eye screening (CONCORDIA) study paper 1 - Scanlon, PH; Gruszka-Goh, M; Javed, U; Vukic, A; Hapeshi, J; Chave, S; Galsworthy, P; Vallance, S; Aldington, SJ (Springer Nature [academic journals on nature.com], 2024)
Objective: This project was to determine the performance of the Zeiss Clarus 700 (Clarus) and the Optos California (Optos) with staged mydriasis in a Diabetic Eye Screening Programme (DESP). Methods: Trial participants were recruited from people attending appointments in DESP or Virtual Eye clinics for delayed hospital appointments. Non-mydriatic photographs from the Clarus and Optos cameras were compared to 2-field 45 degrees mydriatic digital photography (the reference standard) and mydriatic photographs compared if the non-mydriatic photos were unassessable (staged mydriasis). Results: 1573 patients were recruited. 76 individuals were withdrawn, leaving 1497 individuals (2993 eyes). For the Clarus and the Optos, the sensitivity for any retinopathy were 94.2% (95% CI: 92.9–95.3%) and 91.9% (95% CI: 90.5–93.2%) with specificities of 87.3% (95% CI: 85.4–89.0%) and 78.1% (95% CI: 75.7–80.3%) respectively. For referable DR the sensitivities for the Clarus and Optos were 86.0% (95% CI: 82.9–88.8%) and 77.6% (95% CI: 73.9–80.9%) with specificities of 92.8% (95% CI: 91.7–93.8%) and 95.4% (95% CI: 94.5–96.2%) respectively. The Clarus and Optos without mydriasis produced 100 (3.3%) and 152 (5.1%) unassessable eyes respectively, and after staged mydriasis 51 (1.7%) and 102 (3.4%) respectively with 52 (1.7%) reference standard images unassessable. Conclusions: This study reports the performance of the Clarus and the Optos using staged mydriasis in DR screening with wider fields detecting more referable retinopathy peripherally with some reduction in sensitivity centrally for macular lesions.